(untitled) - Albright, William Foxwell (ed.); Freedman, David Noel (ed.); Levine, Baruch A. (New York, 2000)
.AB: Map of Israel on both sides of the Jordan and in the Bashan, Map of Evidence from the Moabite stele on numbers 21, Map of Two alternative routers from Kadesh to the Plains of Moab, Map of Greater Canaan (Numbers 34:1-12)
No.4A
Keywords: Bible Old Testament - Numbers; Freedman, David Noel (ed.); Levine, Baruch A